As representações sociais sobre as vítimas para os autores de violência sexual contra crianças e adolescentes - Esber, Karen Michel (2015)
The main theme of this thesis has its center in the analysis of social representations about the victims of sexual violence in the conception of twenty-six authors of sexual violence (AVS) against children and adolescents, imprisoned in Prison Coronel Odenir Guimarães (POG), in the city of Aparecida Goiânia, State of Goiás, Brasil. The qualitative approach methodology leads the investigative task and the theoretical support searches the knowledge of Social Sciences and the Social Representation Theory, which rise the reflection beyond the individual, considering the conceptual, historical, scientific, media, legal and institutional contexts. The presentation of the interviewees is based on two perspectives: the prison institution, through documentary research in the records of the AVS and the interviewees from sixty-one personal contacts "interviewer-interviewees", mixed by the formal conduct characterized by the filling of the standard questionnaire and dialogues, both purposely targeted the themes: life history, sexualities (for themselves and their victims), children and adolescents, practiced and suffered sexual violence, victims of sexual violence, among others, like the moments of encouragement to free events and narratives of AVS. The result of the interviews showed two constants among AVS, from the empirical field: most categorize people who practice sexual violence as monsters, sick or abnormal and the different facets between denying and assuming the violence. From the perspective of the author of this document, the analysis of the AVS´s social representations about the victims elected three units of meaning: victims and victims of sexual violence, children/adolescents and sexuality (of victims and AVS). The main findings indicate that respondents recognize children and adolescents who experience sexual contact with adults as victims, relation named as a violence and a morally reprehensible act; list harmful consequences of sexual violence for the victims and also for themselves, showing their inseparability; present contradiction between not distinguishing categories as children and adolescents (both represented as biological immature, mental and emotional) and rank crimes from age category; nominate children and adolescents in sexual interaction with adults as innocent, seductive and co-authors, but always victims; show that sexual desire, if any, is directed only to the victims of the violence they committed, and not to other children and adolescents; show crystallization of the role as an author and victim of violence from the gender category; report various negative emotions about themselves in relation to the sexual violence they practiced and the caused consequences in the lives of their victims, such as repentance, disgust, anger, guilt, shame, self-image of monstrosity. Their representations are similar with the three concepts parameters adopted and with those produced and reproduced by common sense, media, law, literature and institutional discourses. The findings shown in this work and the analytical approach used inquire the assertion of part of the international literature on the fact that the AVS fail to recognize the emotional needs of their victims, because they would present empathy deficits toward them, explaining the problem in a strictly intrapsychological bias. Finally, and based on authors of the areas of Social Sciences, appears as necessary the exercise of a new interpretation that links between individual and social experience of AVS to the dominant psychosocial theories, as a contribution to the field of specialized Brazilian studies on the AVS, as well as provide professionals the minimum knowledge to the treatment in the legal field, and treatment in the field of physical and mental health of AVS, in here seen beyond the stereotypes that are charged on them before being on trial.